2022
DOI: 10.3889/oamjms.2022.7017
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Education to the Nutritional Maternal Knowledge and Iron Intake among Toddlers with Anemia

Abstract: BACKGROUND: In general, maternal knowledge about nutrition and health affects food habits, influencing the child’s nutritional or iron intake. One effort to improve children’s iron status is by providing maternal nutrition education. AIM: The purpose of this study was to analyze the effect of a nutrition education intervention on maternal knowledge and toddlers’ iron intake to prevent anemia among children under five. Paired t-test was used to analyze differences in knowledge, nutrient intake, consumption of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
2
1
1
Order By: Relevance
“…Regarding counseling, our study found that women who did not receive dietary counseling during ANC visit had no statistically significant association with hemoglobin levels, which is consistent with a study done in Indonesia 87 but inconsistent with a study conducted in Ethiopia. 88 A plausible explain this discrepancy, it is possible that the quality and content of dietary counseling received may vary.…”
Section: Discussioncontrasting
confidence: 76%
“…Regarding counseling, our study found that women who did not receive dietary counseling during ANC visit had no statistically significant association with hemoglobin levels, which is consistent with a study done in Indonesia 87 but inconsistent with a study conducted in Ethiopia. 88 A plausible explain this discrepancy, it is possible that the quality and content of dietary counseling received may vary.…”
Section: Discussioncontrasting
confidence: 76%
“…Pada saat ini terjadi pertumbuhan dan perkembangan yang cepat sehingga kebutuhan nutrisinya harus dapat terpenuhi dan seimbang. Stunting memiliki hubungan yang erat dengan pertumbuhan dan perkembangan anak dan memberikan pengaruh yang sangat besar terhadap pertumbuhan dan perkembangannya (Fitri et al, 2021;Suryana et al, 2022). Apabila terdapat keterlambatan dalam proses pertumbuhan dan perkembangan di masa emas tersebut akan membahayakan di masa mendatang terutama saat bertumbuh menjadi remaja dan dewasa (Chidumwa et al, 2021;Himaz, 2018).…”
Section: Abstrakunclassified
“…The food consumption of toddlers living in urban areas is more diverse than that in rural areas (Utami & Mubasyiroh, 2020). The increased diversity in child food consumption can also be due to the mother's or caregiver's knowledge and educational factors (Frempong & Annim, 2017;Rahmadi et al, 2022;Suryana et al, 2022). Mothers with sufficient education and knowledge will understand the importance of balanced nutrition to provide the best food for their children.…”
Section: 6mentioning
confidence: 99%
“…Mothers with sufficient education and knowledge will understand the importance of balanced nutrition to provide the best food for their children. Studies have shown that providing various foods can improve babies' nutrition and health (Darawati et al, 2020;Frempong & Annim, 2017;Suryana et al, 2022).…”
Section: 6mentioning
confidence: 99%